2007
DOI: 10.1007/s12079-007-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibitor of MEK-mediated cross-talk between ERK and p38 MAPK during differentiation of human osteosarcoma cells

Abstract: Osteosarcoma is the most common primary malignant bone tumor, accounting for approximately 20% of all primary sarcomas in bone. Although treatment modalities have been improved over the past decades, it is still a tumor with a high mortality rate in children and young adults. Based on histological considerations, osteosarcoma arises from impaired differentiation of these immature cells into more mature types and that correction of this impairment may reduce malignancy and increase the efficiency of chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 38 publications
(47 reference statements)
8
34
0
Order By: Relevance
“…SaOS-2 cells pretreated with PD98059, which inhibits ERK1/2 phosphorylation by preventing MEK1 activation [28], contained much more Dlx5 mRNA than untreated cells. These results agree well with those of Shimo et al [49], who showed that adding PD98059 promotes the early stages of SaOS-2 cell differentiation induced by serum. Further, SaOS-2 cells pretreated with PD98059 and then with BMP-2 also contained more Osx transcripts than did similar cells incubated with BMP-9 alone.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…SaOS-2 cells pretreated with PD98059, which inhibits ERK1/2 phosphorylation by preventing MEK1 activation [28], contained much more Dlx5 mRNA than untreated cells. These results agree well with those of Shimo et al [49], who showed that adding PD98059 promotes the early stages of SaOS-2 cell differentiation induced by serum. Further, SaOS-2 cells pretreated with PD98059 and then with BMP-2 also contained more Osx transcripts than did similar cells incubated with BMP-9 alone.…”
Section: Discussionsupporting
confidence: 93%
“…There have been several reports that state that p38 is also involved in osteoblast differentiation [35,49]. Shimo et al [49] showed that SaOS-2 cells in a medium containing 10% FBS contained fewer type I collagen and fewer ALP transcripts when treated with a p38 inhibitor than did untreated cells.…”
Section: Discussionmentioning
confidence: 99%
“…We note that the inhibition of p38 is predicted to increase survival, consistent with experimental observations 57, 76, 77. However, the observation that Erk and Stat3 have an important role in LNCaP cells57 is not verified, as it has no influence on survival in the model.…”
Section: Biological Applications Of Logic Modelingsupporting
confidence: 76%
“…P38 is frequently linked to inflammation and apoptosis, while ERK often plays a role in survival and proliferation [11,13]. Although the P38 and ERK pathways may appear to play opposing roles, many researchers have shown that there is a substantial amount of crosstalk between these pathways [14,15]. It is the balance between ERK and P38 activation that helps a cell decide between cell division or cell cycle arrest, to promote or inhibit inflammation, and life or death.…”
mentioning
confidence: 99%